Design and implementation of an intrusion-tolerant application server middleware - GUO Yuan-bo; LIU Wei; YUAN Shun; ZHOU Rui-peng (Tongxin xuebao)
An intrusion-tolerance middleware model based on the interceptor was proposed, with a component named intrusion-tolerance framework which logically divided the intrusion-tolerance functions into service providers and service management.The system analyses were designed by adapting intrusion tolerance security model and element technology, the theory of intrusion tolerance mechanism and the strategy of implementation were described, and the intrusion tolerance technology and implementation method was extracted.Finally, an intrusion-tolerance J2EE middleware was realized, built on JBoss-an open source J2EE application server platform, and was implemented through Java class load mechanism with the dynamic load of the intrusion-tolerance class.